Navigating the landscape of mitochondrial-ER communication in health and disease - Ronayne, Conor T.; Latorre-Muro, Pedro (Frontiers in Molecular Biosciences, 2024)
Intracellular organelle communication enables the maintenance of tissue homeostasis and health through synchronized adaptive processes triggered by environmental cues. Mitochondrial-Endoplasmic Reticulum (ER) communication sustains cellular fitness by adjusting protein synthesis and degradation, and metabolite and protein trafficking through organelle membranes. Mitochondrial-ER communication is bidirectional and requires that the ER-components of the Integrated Stress Response signal to mitochondria upon activation and, likewise, mitochondria signal to the ER under conditions of metabolite and protein overload to maintain proper functionality and ensure cellular survival. Declines in the mitochondrial-ER communication occur upon ageing and correlate with the onset of a myriad of heterogeneous age-related diseases such as obesity, type 2 diabetes, cancer, or neurodegenerative pathologies. Thus, the exploration of the molecular mechanisms of mitochondrial-ER signaling and regulation will provide insights into the most fundamental cellular adaptive processes with important therapeutical opportunities. In this review, we will discuss the pathways and mechanisms of mitochondrial-ER communication at the mitochondrial-ER interface and their implications in health and disease.